A Diabetic Patient Complicated With Pancreatic Cancer After Using Liraglutide: A Case Report - Wu, Shengjie; Wang, Jiabing; Jing, Li; Chen, Liping (Frontiers in Endocrinology, 2021)
Background: Diabetes and cancer are both multifactorial diseases, and epidemiologic evidence indicates that diabetes may be associated with the incidence of certain types of cancer. In diabetes the risk of pancreatic cancer is increased significantly. However, whether certain diabetes treatment being related with the risk of pancreatic cancer remains unclear. In this report, we presented a case of pancreatic ductal adenocarcinoma in a diabetic patient in China after being treated with liraglutide, a novel glucagon-like peptide-1 (GLP-1) analog. Case report: A 71-year-old Han Chinese man who had had a type 2 diabetes for 25 years presented at the endocrinology department with discomfort in the left upper quadrant of abdomen for 10 days. The patient’s vital signs and laboratory findings were unremarkable except for the elevated level of carbohydrate antigen (CA19-9). The upper abdomen routine enhanced computed cosmography (CT) scan showed low density of the pancreatic body and tail, and the histopathological result of the pancreatic biopsy samples was pancreatic ductal adenocarcinoma with regional lymph node metastasis. We reviewed his former medical records and found that liraglutide was added to his hypoglycemic treatment regimen 20 months ago. At that time, the level of tumor biomarkers and upper abdomen routine CT were unremarkable. We estimated the causality between liraglutide and pancreatic cancer by the Naranjo Adverse Drug Reaction Probability scale and WHO-Uppsala Monitoring Centre (WHO-UMC) system, and the causality turned out to be possible. Conclusion: Our report suggests that liraglutide may be related with the genesis and development of pancreatic cancer and also highlights the importance of regular checkups in diabetic patients treated with liraglutide. However, our report has some notable limitations, and further longer term follow-up trails with larger sample should be conducted in future to assess the causality between liraglutide and pancreatic cancer.